IN VITRO FLOWER INDUCTION AND MULTIPLE SHOOT REGENERATION STUDIES IN CYPERUS SCARIOSUS R.Br FROM AXILLARY BUD EXPLANTS - K. LAVANYA; R. CHAKRAVARTHY; M.S.R. KRISHNA (International Journal of Pharma and Bio Sciences, 2014)
Cyperus scariosus R.Br is a valuable multipurpose medicinal herb, which belongs to family Cyperaceae. It possesses astringent, anti-inflammatory, diaphoretic, diuretic, cordial and stomach ache properties. An attempt has been made to study in vitro regeneration, floral bud induction, multiple shooting and multiple rooting has been achieved via healthy, moderate axillary buds as explants. The axillary bud explants were inoculated on Schenk and Hildebrandt medium with various concentrations of BA (0.5-2.0mg/lt) and Kn (0.5-2.0mg/lt) for in vitro regeneration. Effective, healthy shoots were observed from Kn 0.75mg/lt with activated charcoal 500mg/lt. These shoots were further subculture on Kn 0.75mg/lt with various concentrations of Adenosine (ADS) 0.5-2.0mg/lt and activated charcoal 500 mg/lt. Efficient flowering 80% was noted on SH media, when supplemented with Kn 0.75mg/lt+ADS 1.0mg/lt+activated charcoal 500 mg/lt. 98% of multiple shooting and multiple rooting was effective on full strength SH medium supplemented with Kn1.5mg/lt+ADS1.0mg/lt+ activated charcoal 500mg/lt+5% coconut water. In vitro regenerated plantlets were transferred onto vermiculite pots, which were further acclimatized in the field.